Histopatologi Insang Ikan Bandeng (Chanos chanos) yang tertangkap di Muara Tukad Badung, Bali - Sari, Alfi Hermawati Waskita (Journal of Marine and Aquatic Sciences; Vol 5 No 2 (2019), 2018)
This study demonstrates the usefulness as a bio-indicator of milkfish ( Chanos chanos ), which are often caught in the TukadBadung Estuary Bali. Information regarding the histopathology gill organs of milkfish provides important early information for use in biomonitoring efforts to make ecosystems sustainable. The measurement results of heavy-metal Leads at Station III (0,0101 mg/L) exceeded the water quality standard threshold based on the KepMen Negara LH No. 51 Tahun 2004 standard for seawater quality (seawater biota). The results of the observation of the histopathological features of milkfish gills caught in Muara Tukad Badung revealed oedema, hyperplasia, hypertrophy fusion of the gill lamellae, Lifting ephitelium and telangiectasis.